2013
DOI: 10.1155/2013/626083
|View full text |Cite
|
Sign up to set email alerts
|

Ultradeep Pyrosequencing of Hepatitis C Virus Hypervariable Region 1 in Quasispecies Analysis

Abstract: Genetic variability of hepatitis C virus (HCV) determines pathogenesis of infection, including viral persistence and resistance to treatment. The aim of the present study was to characterize HCV genetic heterogeneity within a hypervariable region 1 (HVR1) of a chronically infected patient by ultradeep 454 sequencing strategy. Three independent sequencing error correction methods were applied. First correction method (Method I) implemented cut-off for genetic variants present in less than 1%. In the second meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Previous studies have sought to characterise the mutagenic effect of RBV using conventional sequencing methods, and have revealed that HCV infection comprises a cloud of closely related sequence variants differing by as little as one nucleotide from a population average sequence. Pyrosequencing techniques make it possible to detect all the genomic variants of the viral population and offer a new and useful approach in HCV research [Caraballo Cortes et al, ]. In order to confirm previous research results using direct sequencing, in the present study, the complete NS5A region of the baseline sample was pyrosequenced, at four weeks after ribavirin monotherapy, in a patient chosen at random.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have sought to characterise the mutagenic effect of RBV using conventional sequencing methods, and have revealed that HCV infection comprises a cloud of closely related sequence variants differing by as little as one nucleotide from a population average sequence. Pyrosequencing techniques make it possible to detect all the genomic variants of the viral population and offer a new and useful approach in HCV research [Caraballo Cortes et al, ]. In order to confirm previous research results using direct sequencing, in the present study, the complete NS5A region of the baseline sample was pyrosequenced, at four weeks after ribavirin monotherapy, in a patient chosen at random.…”
Section: Discussionmentioning
confidence: 92%
“…The newly available pyrosequencing technique opens up a new approach to the analysis of complex viral genomes, by enabling the detection of rare molecular variants and thus a better understanding of genetic variability. This approach has been applied successfully in studies of the human immunodeficiency virus, but very few studies have used it with respect to HCV [Nasu et al, ; Caraballo Cortes et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…At intra-host level, HCV exists as quasispecies defined by several closely related yet genetically distinct populations mainly because of low viral RNA polymerase fidelity (Bittar et al, 2013;Caraballo Cortes et al, 2013). The mechanisms driving HCV quasispecies diversification are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…With nextgeneration sequencing (NGS) platforms, it is now possible to investigate viral quasispecies at much greater detail. Their high throughput allows for generation of millions of reads in a single sequencing run, facilitating indepth sequencing [22]. These new methods can detect variants at low frequencies, which would go undetected by standard sequencing methods [23].…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain insight into these matters, we have performed a Bayesian coalescent analysis of HVR1 sequences of a HCV quasispecies population circulating in a chronic patient infected with HCV genotype 1b recently obtained by ultra-deep sequencing [22]. The results of these studies highlight the importance of minority genomes in HCV population history and evolution, the mutant clouds as reservoirs of phenotypic and genetic variants for virus adaptability, as well as the roll of the mutant spectra to overcome selective constraints.…”
Section: Introductionmentioning
confidence: 99%